Cell Line Characteristics Predict Subsequent Resistance to Androgen Receptor-Targeted Agents (ARTA) in Preclinical Models of Prostate Cancer - Moll, Jan Matthijs; Teubel, Wilma J.; Erkens, Sigrun E.; Jozefzoon-Agai, Ashraf; Dits, Natasja F.; van Rijswijk, Angelique; Jenster, Guido W.; van Weerden, Wytske M. (Frontiers in Oncology, 2022)
Treatment of prostate cancer (PCa) has changed considerably in the last decade due to the introduction of novel androgen receptor targeted agents (ARTA) for patients progressive on androgen deprivation therapy (ADT). Preclinical research however, still relies heavily on AR-negative cell line models. In order to investigate potential differences in castration-resistant PCa (CRPC) growth, we set out to create a comprehensive panel of ARTA-progressive models from 4 androgen responsive, AR wild-type PCa cell lines, and analysed their androgen response as opposed to their ADT-progressive counterparts. Parallel cultures of VCaP, DuCaP, PC346C and LAPC4 were established in their respective culture media with steroid-stripped FCS (DCC) without androgen (ADT) or in DCC plus 1 uM of the AR targeted agents (ARTA) bicalutamide, OH-flutamide or RD162 (an enzalutamide/ apalutamide analogue). Cell growth was monitored and compared to parental cell lines. Short-term androgen response was measured using cell proliferation MTT-assay. qRT-PCR was performed to assess mRNA expression of markers for AR signalling, steroidogenesis, GR signalling, EMT and WNT signalling. Out of 35 parallel cultures per cell line, a total of 24, 15, 34 and 16 CRPC sublines emerged for VCaP, DuCaP, PC346C and LAPC4, respectively. The addition of bicalutamide or OH-flutamide significantly increased CRPC growth compared to ADT or RD162. VCaP, DuCaP and PC346C CRPC clones retained an AR-responsive phenotype. Expression of AR and subsequent androgen response was completely lost in all LAPC4 CRPC lines. Markers for EMT and WNT signalling were found to be elevated in the resilient PC346C model and CRPC derivatives of VCaP, DuCaP and LAPC4. Although the resistant phenotype is pluriform between models, is seems consistent within models, regardless of type of ARTA. These data suggest that the progression to and the phenotype of the CRPC state, might already be determined early in carcinogenesis.